Людинознавство як джерело пізнання і розвитку лідерства - Лозовой, Віктор; Долгарев, Анатолій Васильович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Розглянуто необхідність становлення лідера, розгортання його управлінського потенціалу передбачає необхідність і значущість системних знань про людину на біофізіологічному, соціально-психологічному та духовному зрізах. Обґрунтовано необхідність подальшого поглиблення системних знань у науковому напрямку «Людинознавство» і важливість включення такої навчальної дисципліни у навчальні плани закладів середньої і вищої освіти України.

In the management of organizations, work teams, the personality of the leader is of great importance. The presence of a leader, his leadership qualities helps to effectively solve the problems of the functioning of organizations, labor collectives, to achieve their goals. The formation of a leader, the development of his managerial potential implies the necessity and significance of systemic knowledge about a person at the biophysiological socio-psychological and spiritual levels. The article substantiates the need for further deepening of systemic knowledge in the scientific direction of "Humanity" and the importance of including such an academic discipline in the curricula of educational institutions of secondary and higher education in Ukraine.
Human knowledge as a source of knowledge and development of leadership
Keywords: керівництво; управління; взаємодія лідера і команди; manager; management; leader and team interaction